Acute caffeine supplementation enhances several aspects of shot put performance in trained athletes - Verónica Giráldez-Costas; Millán Aguilar-Navarro; Jaime González-García; Juan Del Coso; Juan José Salinero (Taylor & Francis Group, 2022)
The aim of this investigation was to determine the effect of a moderate dose of caffeine (3 mg/kg/b.m.) on muscular power and strength and shot put performance in trained athletes. Methods. Thirteen shot putters (eight men and five women) participated in a double-blind, placebo-controlled, randomized experiment. In two different trials, participants ingested either 3 mg/kg/b.m. of caffeine or a placebo. Forty-five min after substance ingestion, athletes performed a handgrip dynamometry test, a countermovement jump (CMJ), a squat jump (SJ), and a maximum-velocity push-up. The athletes also performed three types of throws: a backwards throw, a standing shot put and a complete shot put. Results. In comparison with the placebo, caffeine ingestion increased CMJ height (32.25 ± 7.26 vs. 33.83 ± 7.72 cm, respectively; effect size (ES) = 0.82, p = 0.012; +5.0%;) and SJ height (29.93 ± 7.88 vs. 31.40 ± 7.16 cm; ES = 0.63, p = 0.042; +6.4%) and distance in the standing shot put (10.27 ± 1.77 m vs. 10.55 ± 1.94 m; ES = 0.87, p = 0.009; +2.6%). However, caffeine ingestion did not increase strength in the handgrip test, power in the ballistic push-up, or distance in the backwards throw (all p > 0.05). Shot put performance changed from 11.24 ± 2.54 to 11.35 ± . 2.57 m (ES = 0.33, p = 0.26; +1.0%), although the difference did not reach statistically significant differences. Caffeine ingestion did not increase the prevalence of side effects (nervousness, gastrointestinal problems, activeness, irritability, muscular pain, headache, and diuresis) in comparison with the placebo (p > 0.05). Conclusion. In summary, caffeine ingestion with a dose equivalent to 3 mg/kg/b.m. elicited moderate improvements in several aspects of physical performance in trained shot putters but with a small effect on distance in a complete shot put.